Pedagogical Ability of Islamic Religious Education Teachers in Using Learning Media - Lubis, Dede Efrianti (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
This study aimed to describe the pedagogical ability of Islamic religious education teachers in using learning media at SMA Swasta Dharmawangsa Medan SMA Islam Swasta An-Nizam Medan. This research is qualitative with a multisite model. The research data is Islamic education teachers' pedagogical ability to use learning media. Data collection techniques are observation, interview, and documentation. At the same time, data analysis is done through data reduction, data presentation, conclusion drawing, and data verification. The results of the study explained that in planning, PAI teachers at Dharmawangsa Private Senior High School Medan An-Nizam Private Islamic High School Medan must consider learning objectives, characteristics of students, and available resources. They must also choose media that are relevant to the subject matter and able to facilitate interactive learning. In addition, implementing the use of learning media also requires careful preparation regarding technology and infrastructure. In media-based learning, learners have the opportunity to learn through experience and enrich their understanding through the use of images, videos, and animations. Media also allows learners to access content independently, enabling them to learn the material at their own pace. However, media use can also present obstacles for PAI teachers at SMA Swasta Dharmawangsa Medan SMA Islam Swasta An-Nizam Medan. For example, the media used must be well-designed not to confuse or distract learners. In addition, some learners may need help accessing the media due to technological limitations or lack of access to the necessary resources. The impact of using learning media on learner engagement can be very beneficial. However, media use also requires careful preparation and patience in overcoming technical and practical obstacles. Therefore, PAI teachers must consider the benefits and challenges of media use before using it in learning at SMA in SMA Swasta Dharmawangsa Medan SMA Islam Swasta An-Nizam Medan.